Improving Environmental Outcomes With Games: An Exploration of Behavioural and Technological Design and Evaluation Approaches. (October 2022) - de Salas, Kristy; Ashbarry, Louise; Seabourne, Mikaela; Lewis, Ian; Wells, Lindsay; Dermoudy, Julian; Roehrer, Erin; Springer, Matthew; Sauer, James D.; Scott, Jenn
Background: To overcome the high failure rate of gameful interventions, we need to better understand their design and evaluation strategies to build an evidence-base for best-practice approaches that bring about meaningful change. This systematic review asks: 'What behavioural and technological design and evaluation theories and approaches are applied in games developed to bring about positive environmental outcomes?'. Method: We reviewed 52 papers published between 2015 and 2020 that used gameful interventions to improve behaviour related to environmental outcomes. These papers were analysed to review the behavioural and technical design, and the assessment and evaluation approaches, employed by the intervention designers. Results: We found that these publications report on simple aspects of the behavioural and technical design behind the intervention but fail to justify their design choices in terms of theory and evidence. Furthermore, variability across their evaluation approaches and outcomes exists. Discussion: This review highlights several systemic flaws in the literature that limit our understanding of gameful interventions in the pro-environmental context. First, based on this review, we cannot be convinced that these interventions were designed according to best practice for intervention design or for technology development. Second, the justification for proposing a gameful intervention is not always clear. Finally, it is unclear whether these interventions are being evaluated based on best practice. Thus, it is not clear that we can draw confident conclusions about evidence-based outcomes of short-term engagement (in structural gamification interventions) or long-term behaviour change (in content gamification and serious game interventions).